Flouting Of Maxim In Comedi Moderen Gokil Movie: A Pragmatics Review - Suhardianto Suhardianto (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
Flouting maxim is one of flout language kinds that usually happened in social community. The aim of this research is to find out the kinds of flouting maxim usage in komedi moderen gokil. This research uses qualitative method due to analyze data does not statistic but words description. In data collection, researcher uses primary and secondary data. Researcher uses observation method. According to Sudaryanto (1998:33) observation method is the same as simak method. The technique used is simak bebas libat cakap. In analyzing data, the researcher uses padan technique. The researcher found 20 data that are classified into four kinds of flouting maxim in comedi moderen gokil movie. They are flouting maxim quality, flouting maxim quantity, flouting maxim relevant and flouting maxim manner. Researcher found that the most flouting maxim used is flouting maxim of relevant and the most rarely used is flouting maxim of manner. Beside, the researcher found the domain language of flouting maxim in comedi moderen gokil movie namely domain working, domain family, domain holiday and domain dance place.